Geographical distribution of irrigation techniques in Salah al-Din overnorate - Mohammed, Hakam Thyab; Abdel Razzaq, Mathil Arif (Journal of Tikrit University for Humanities, 2024)
The study dealt with the geographical distribution and classification of irrigation techniques used in the study area which is Salah al-Din Governorate, for the year 2022. The study area is one of the distinguished Iraqi governorates in agricultural production, especially the cultivation of grain crops, whose cultivation expanded in the governorate during the last period of (2010- 2022). This resulted through the use of modern technologies in agricultural production, especially sprinkler irrigation technologies, which achieved great development in the cultivation of grain crops and contributed to their development, as the study area has (5401) pivot sprinklers and approximately (5296) fixed irrigation systems. Additionally, there were (39,537) drip irrigation systems distributed across the districts of the study area, and their distribution varied. This is due to a group of natural and human factors that affect their distribution from one place to another. Natural and human factors have a significant role in influencing distribution and the use of sprinkler and drip irrigation techniques. The most prominent of these human factors are government policy, low government support, and high prices for purchasing systems, as well as the cultural and social levels of farmers. The study assumed the existence of a discrepancy between the districts of the study area in the distribution of irrigation techniques due to multiple natural and human reasons. The study aims to explain the types of irrigation techniques, as well as determining the distribution of these techniques across the districts of the study area, as well as explaining the reasons for this discrepancy and the most important problems and obstacles resulting from this distribution.